Diaphragm for alkaline electrolyzed water and preparation method thereof
By using technical means of halomethylation treatment and crosslinking reaction in alkaline electrolytic water separators, the toughness and gas barrier of the separators are significantly improved, and the problems of low mechanical strength and high energy consumption of traditional separators are solved, achieving a more efficient and reliable hydrogen production process for electrolytic water.
Patent Information
- Application Number
- CN202411906359.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional alkaline electrolytic diaphragms have low mechanical strength and poor toughness, which are prone to cracking, resulting in a decrease in airtightness and increasing the risk of hydrogen leakage. At the same time, the toughening agent improves mechanical properties will affect the hydrophilicity of the diaphragm and increase energy consumption.
The coatings including inorganic particles, first type binders, second type binders, pore-forming agents, organic solvents and crosslinking agents are used to significantly enhance the toughness of the membrane and control the surface resistance through halomethylation treatment and crosslinking reaction.
The excellent toughness and low internal resistance of the diaphragm are achieved, which reduces the generation of diaphragm cracks, extends the service life, improves gas resistance, and reduces the energy consumption in the process of electrolyzing hydrogen production.
Smart Images

Figure CN119708588A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite membranes, and in particular to a diaphragm for alkaline water electrolysis and a preparation method thereof. Background Art
[0002] Hydrogen is widely used in petrochemical refining, chemical synthesis, metal smelting, fuel cells and other industries. Electrolysis of water to produce hydrogen is a green and environmentally friendly way to produce hydrogen. With the vigorous development of renewable energy technology, renewable energy water electrolysis hydrogen production technology has received widespread attention.
[0003] As one of the main equipment for hydrogen production by water electrolysis, the alkaline electrolyzer mainly includes key components such as plates, electrodes, and diaphragms. The diaphragm prevents hydrogen and oxygen from diffusing with each other, while allowing the penetration of hydroxide ions and water, so that the electrolysis reaction proceeds quickly and continuously. Therefore, the diaphragm must ensure that ions pass through while also having the characteristics of high temperature resistance, corrosion resistance, low surface resistance, and excellent gas barrier properties. In traditional technologies, diaphragms have low mechanical strength and poor toughness. The diaphragm is prone to cracking during the assembly process and use, resulting in a decrease in the air tightness of the diaphragm, resulting in an increase in the concentration of hydrogen in oxygen, and increasing the risk of hydrogen leakage during the production process of hydrogen production by alkaline water electrolysis.
[0004] In order to improve the toughness of the diaphragm, toughening agents are usually used to improve the mechanical properties of the resin material. Although organic toughening agents can improve the mechanical properties of the resin material, they will affect the hydrophilicity of the water electrolysis diaphragm, thereby increasing the surface resistance of the diaphragm, and further increasing energy consumption in the process of water electrolysis to produce hydrogen. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, one object of the present invention is to provide a diaphragm for alkaline water electrolysis and a preparation method thereof, wherein the diaphragm for alkaline water electrolysis provided by the present invention has both excellent toughness and low internal resistance.
[0006] To this end, the first aspect of the present invention provides a diaphragm for alkaline water electrolysis, comprising a base membrane and a coating provided on at least one side of the base membrane, wherein the preparation of the coating comprises the following raw material components: inorganic particles, a first type of binder, a second type of binder, a pore-forming agent, an organic solvent and a cross-linking agent, wherein the second type of binder comprises one or more of halogenated polysulfone, halogenated polyether sulfone and halogenated polyphenyl sulfone.
[0007] The diaphragm for alkaline water electrolysis proposed by the present invention contains a second type of binder in its raw material components. The second type of binder is obtained by introducing a halomethyl group into a polymer, performing a halomethylation treatment, opening the polymer chain, and then introducing a cross-linking agent for chain segment cross-linking, which can significantly enhance the toughness of the diaphragm, and the surface resistance of the diaphragm is small, which can reduce the generation of diaphragm cracks, is conducive to increasing the service life of the diaphragm, and improving the gas barrier property of the diaphragm.
[0008] In some embodiments of the present invention, the inorganic particles, the first type of binder, the second type of binder, the pore-forming agent and the organic solvent form a casting liquid. Based on the total mass of the raw material components of the casting liquid, the mass proportion of each component is: inorganic particles 29%-60%, first type of binder 4%-30%, second type of binder 5%-11%, pore-forming agent 0.1%-5%, organic solvent 21%-61%.
[0009] In some embodiments of the present invention, the cross-linking agent includes one or more of imidazole, trimethylimidazole, bipyridine, tetramethylethylenediamine and ethylenediamine.
[0010] In some embodiments of the present invention, in the repeating unit of the polymer of the second type of binder, each repeating unit contains 0.5-6 halomethyl groups.
[0011] In some embodiments of the present invention, the inorganic particles include one or more of ZrO2, TiO2, Mg(OH)2, Y2O3, CeO2, HfO2, Zr3(PO4)4, SiC, and BaSO4.
[0012] In some embodiments of the present invention, the first type of binder includes at least one of polysulfone, polyethersulfone, and polyphenylsulfone.
[0013] In some embodiments of the present invention, the organic solvent includes one or more of N-methyl-2-pyrrolidone, N-ethyl-pyrrolidone, N,N-dimethylformamide, formamide, dimethyl sulfoxide, and N,N-dimethylacetamide.
[0014] In some embodiments of the present invention, the pore-forming agent includes one or more of glycerol, polyvinyl pyrrolidone, polyethylene glycol, and polyvinyl alcohol.
[0015] In some embodiments of the present invention, the base film includes one of polypropylene, polyethylene, polysulfone, polyphenylene sulfide, polyamide, polyethersulfone, polyphenylsulfone, polyethylene terephthalate, and polyetheretherketone.
[0016] In the second aspect of the present invention, the present invention proposes a method for preparing the alkaline water electrolysis membrane described in the first aspect, comprising: mixing inorganic particles, a first type of binder, a second type of binder, a pore-forming agent and an organic solvent into a casting solution, symmetrically coating both sides of the base film, forming pores and forming a film, and obtaining an intermediate membrane; dissolving a cross-linking agent in water to prepare a cross-linking agent aqueous solution with a cross-linking agent mass ratio of 5%-20%, cross-linking the intermediate membrane in the cross-linking agent aqueous solution for 10min-30min, and washing with water to obtain an alkaline water electrolysis membrane. As a result, the alkaline water electrolysis membrane prepared by the present invention has excellent toughness and low internal resistance.
[0017] In some embodiments of the present invention, the pore-forming and membrane-forming method is a non-solvent induced phase separation method.
[0018] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The above and / or additional aspects and advantages of the present invention will become clear and easily understood through the description of the embodiments in conjunction with the accompanying drawings, in which:
[0020] Figure 1 The schematic diagram shows the structure of the diaphragm for alkaline water electrolysis proposed in the embodiment of the present invention.
[0021] Description of the accompanying drawings: 100, diaphragm for alkaline water electrolysis; 1, base film; 2, coating. DETAILED DESCRIPTION
[0022] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0023] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0024] In a first aspect of the present invention, the present invention provides a diaphragm 100 for alkaline water electrolysis. Figure 1 The alkaline water electrolysis diaphragm 100 provided in the present invention comprises a base film 1 and a coating 2 provided on at least one side of the base film 1, wherein the coating 2 comprises the following raw material components:
[0025] Inorganic particles, a first type of binder, a second type of binder, a pore former, an organic solvent and a crosslinking agent, wherein the second type of binder comprises one or more of halogenated polysulfone, halogenated polyethersulfone and halogenated polyphenylsulfone.
[0026] The diaphragm 100 for alkaline water electrolysis proposed in the present invention contains a second type of binder in its raw material components. By introducing a halomethyl group into the polymer and performing a halomethylation treatment to open the polymer chain, and then introducing a cross-linking agent to perform segment cross-linking, the toughness of the diaphragm can be significantly enhanced, and the wrinkles and ruptures of the diaphragm during installation can be reduced, thereby reducing safety hazards. In addition, the surface resistance of the diaphragm is small, which can reduce the generation of diaphragm cracks, is beneficial to increasing the service life of the diaphragm, and improving the gas barrier properties of the diaphragm. The electrical performance of the electrolytic cell for alkaline water electrolysis is less affected.
[0027] In some embodiments of the present invention, the inorganic particles, the first type of binder, the second type of binder, the pore-forming agent and the organic solvent form a casting liquid. Based on the total mass of the raw material components of the casting liquid, the mass proportion of each component is: inorganic particles 29%-60%, first type of binder 4%-30%, second type of binder 5%-11%, pore-forming agent 0.1%-5%, organic solvent 21%-61%.
[0028] As an example, the mass proportion of inorganic particles can be 29%, 30%, 40%, 50%, 60%, etc., the mass proportion of the first type of binder can be 4%, 10%, 20%, 30%, etc., the mass proportion of the second type of binder can be 5%, 7%, 10%, 11%, etc., the mass proportion of the pore former can be 0.1%, 1%, 3%, 5%, etc., and the mass proportion of the organic solvent can be 21%, 30%, 40%, 50%, 60%, 61%, etc.
[0029] By controlling the mass proportion of each component within the above range, the toughness and internal resistance of the alkaline water electrolysis membrane 100 can be further taken into account.
[0030] In some embodiments of the present invention, the inorganic particle content ranges from 29% to 60%, which can reduce the poor hydrophilicity of the diaphragm caused by too low an inorganic particle content, and can also reduce the high viscosity of the casting liquid and the difficulty in dispersion caused by too high an inorganic particle content, which is further conducive to obtaining a diaphragm with excellent toughness and low internal resistance.
[0031] In some embodiments of the present invention, the first type of binder can effectively bind inorganic particles and form pores during the preparation of the membrane coating 2. The content of the first type of binder is in the range of 4%-30%, which can reduce the low inorganic particle bonding force and powdering of the membrane coating 2 caused by too low a content of the first type of binder; it can also reduce the deterioration of the hydrophilicity of the membrane caused by too high a content of the first type of binder, which is further conducive to obtaining a membrane with excellent toughness and low internal resistance.
[0032] In some embodiments of the present invention, after halomethylation such as chloromethylation, the second type of binder reacts with the crosslinking agent. The content of the second type of binder is in the range of 5%-11%, which can reduce the insignificant improvement in the toughness of the diaphragm caused by too low a content of the second type of binder, and the susceptibility to cracks; it can also reduce the excessive crosslinking of the reaction caused by too high a content of the second type of binder, increase the density of the diaphragm, increase the surface resistance of the membrane, and reduce the ion conductivity, which is further conducive to obtaining a diaphragm with excellent toughness and low internal resistance.
[0033] In some embodiments of the present invention, the pore-forming agent content ranges from 0.1% to 5%, which can reduce the low porosity of the diaphragm and the high surface resistance of the diaphragm caused by too low a pore-forming agent content; it can also reduce the high porosity of the diaphragm, the large volume shrinkage rate, and the long water washing process time caused by too high a pore-forming agent content, which is further conducive to obtaining a diaphragm with excellent toughness and low internal resistance.
[0034] In some embodiments of the present invention, the organic solvent content ranges from 21% to 61%, which can reduce the low porosity and high surface resistance of the diaphragm caused by too low organic solvent content; it can also reduce the high porosity of the diaphragm caused by too high organic solvent content, increase the gas permeability, and reduce the purity of the anode and cathode gases, which is further conducive to obtaining a diaphragm with excellent toughness and low internal resistance.
[0035] In some embodiments of the present invention, the organic solvent includes one or more of N-methyl-2-pyrrolidone (NMP), N-ethyl-pyrrolidone (NEP), N,N-dimethylformamide (DMF), formamide, dimethyl sulfoxide (DMSO), and N,N-dimethylacetamide (DMAC). The above organic solvents are all commonly used polar solvents. After drying, the organic solvent evaporates to obtain a uniform coating 2. Considering the polymer solubility and cost factors, the organic solvent is preferably NMP.
[0036] In some embodiments of the present invention, the inorganic particles include one or more of ZrO2, TiO2, Mg(OH)2, Y2O3, CeO2, HfO2, Zr3(PO4)4, SiC, and BaSO4. The above inorganic particles are resistant to strong alkali corrosion and have hydrophilic properties. ZrO2 has excellent alkali resistance and cost advantages, and the inorganic particles are preferably ZrO2.
[0037] In some embodiments of the present invention, the first type of binder includes one or more of polysulfone, polyethersulfone, polyphenylsulfone, and polybenzimidazole. Considering the cost and polymer bonding performance, the first type of binder is preferably polysulfone.
[0038] In some embodiments of the present invention, the pore-forming agent includes glycerol, polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), and polyvinyl alcohol (PVA). The pore-forming agent is preferably glycerol. By using the above pore-forming agent, an alkaline water electrolysis membrane 100 with a moderate porosity can be obtained.
[0039] In some embodiments of the present invention, the base film 1 includes one of polypropylene (PP), polyethylene (PE), polysulfone (PS), polyphenylene sulfide (PPS), polyamide / nylon (PA), polyethersulfone (PES), polyphenylsulfone (PPS), polyethylene terephthalate (PET), and polyetheretherketone (PEEK). The base film 1 of the above materials has good thermal stability, good toughness, and low resistance. Considering the harsh conditions of the electrolytic cell under 80°C working conditions, the base film 1 is preferably PPS.
[0040] In some embodiments of the present invention, the cross-linking agent includes one or more of imidazole, trimethylimidazole, bipyridine, tetramethylethylenediamine and ethylenediamine: imidazole, trimethylimidazole, bipyridine, tetramethylethylenediamine and ethylenediamine are all commonly used cross-linking agents in the art. Considering the ease of reaction and cost factors, the cross-linking agent is preferably imidazole.
[0041] In some embodiments of the present invention, in the repeating unit of the polymer of the second type of binder, each repeating unit contains 0.5-6 halomethyl groups, and the chloromethylation degree of the polymer is 0.5-6 halomethyl units in each repeating unit. For example, it contains 0.5, 1, 3, 5, 6 halomethyl units, etc., so that the insufficient cross-linking reaction caused by too few halomethyl units and the poor toughness of the diaphragm can be reduced; the increase in the density of the diaphragm caused by too many halomethyl units, the decrease in pore size, the increase in the surface resistance of the membrane, and the easy destruction of the polysulfone structure under alkaline conditions, and the poor dimensional stability of the diaphragm can also be reduced.
[0042] In a second aspect of the present invention, the present invention provides a method for preparing the alkaline water electrolysis membrane 100 described in the first aspect, comprising:
[0043] S1, mixing inorganic particles, a first type of binder, a second type of binder, a pore-forming agent and an organic solvent into a casting solution, symmetrically coating the solution on both sides of the base film 1, forming pores to form a film, and obtaining an intermediate film;
[0044] S2. Dissolve the crosslinking agent in water to prepare a crosslinking agent aqueous solution with a crosslinking agent mass ratio of 5%-20%, crosslink the intermediate film in the crosslinking agent aqueous solution for 10min-30min, and then wash with water to obtain the alkaline electrolysis water diaphragm 100.
[0045] Therefore, the alkaline water electrolysis membrane 100 prepared by the present invention has both excellent toughness and low internal resistance.
[0046] In some embodiments of the present invention, the concentration of the aqueous solution of the cross-linking agent is 5%-20%, for example, it can be 5%, 10%, 15%, 20%, etc., and controlling the mass proportion of the cross-linking agent within the above range can reduce the insufficient cross-linking reaction and poor toughness of the diaphragm caused by too low cross-linking agent concentration; it can also reduce the content of more unreacted cross-linking agent inside the diaphragm caused by too high cross-linking agent concentration, which prolongs the post-processing cleaning time and reduces production efficiency.
[0047] In some embodiments of the present invention, the cross-linking reaction time is 10-30 minutes. For example, the cross-linking reaction time can be 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, etc. By controlling the cross-linking reaction time within the above range, it is possible to reduce the inadequate reaction caused by too low a cross-linking reaction time and the poor toughness of the diaphragm; it is also possible to reduce the excessive cross-linking caused by too long a cross-linking reaction time, which increases the density of the diaphragm, reduces the pore size, and increases the surface resistance of the membrane.
[0048] In some embodiments of the present invention, the pore-forming membrane is formed by non-solvent induced phase separation. NIPS is the abbreviation of non-solvent induced phase separation, also known as wet method. Its process flow is to dissolve the polymer in the solvent to form a homogeneous solution, then slowly add a reagent with stronger miscibility with the solvent (called an extractant) to extract the solvent, forming a two-phase structure with the polymer as the continuous phase and the solvent as the dispersed phase, and then remove the solvent to obtain a polymer with a certain pore structure. The above method is a commonly used method for preparing porous diaphragms.
[0049] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.
[0050] The halomethylation of the second type of binder polymer is a well-known technique in the art. Taking polysulfone as an example, the preparation method of chloromethylated polysulfone is as follows:
[0051] (1) Slowly add 5 g of polysulfone into a three-necked flask containing 300 ml of dichloromethane under stirring to fully dissolve it;
[0052] (2) Then, a certain proportion of chloromethyl methyl ether and anhydrous SnCl2 as a catalyst were slowly added, and the mixture was reacted at 50°C for 20 hours;
[0053] (3) After the reaction is completed, chloromethylated polysulfone is obtained after precipitation, washing and drying.
[0054] Example 1
[0055] (1) 15% of the first type of binder polysulfone and 8% of the second type of binder chloromethylated polysulfone and 40% of the organic solvent NMP are fully stirred and dissolved at 100° C. to prepare a binder solution;
[0056] (2) the binder solution and the organic solvent are fully mixed and dissolved, and then 3% of pore-forming agent glycerol and 34% of inorganic particles ZrO2 are added in sequence to form a casting solution;
[0057] (3) Dispersing the casting solution in a planetary disperser for 1-3 hours;
[0058] (4) coating the evenly dispersed casting solution on the polymer PPS base film by double-sided dip coating;
[0059] (5) cross-linking the membrane obtained in step (4) in an aqueous solution of 12.5% cross-linking agent imidazole for 20 minutes;
[0060] (6) The cross-linked membrane is pore-formed in a gas phase and in a coagulation bath, respectively, and finally washed with deionized water to form an alkaline hydrogen production membrane.
[0061] The method for preparing the coated diaphragm in Examples 2-10 and Comparative Examples 1-3 is the same as that in Example 1 above, but the specific coating slurry formula is different, see Table 1.
[0062] Table 1
[0063]
[0064]
[0065] The following tests were performed on the diaphragms obtained in Examples 1-10 and Comparative Examples 1-3:
[0066] (1) Surface resistance test:
[0067] After different electrolysis times, the diaphragm was taken out from the electrolytic cell and the surface resistance was tested. The surface resistance was tested by electrochemical impedance spectroscopy, and the test electrode was a two-electrode system. A 20mm×20mm square test port was set in the middle of two polytetrafluoroethylene plates, and two nickel sheets (20mm×20mm×0.5mm) were placed in the test port. The diaphragm sample was placed in the middle of the nickel sheet, and the diaphragm was 3mm away from the nickel sheet. The polytetrafluoroethylene plate was tightly fixed with polytetrafluoroethylene screws and nuts. Place it in a beaker containing 30wt% KOH solution for 24h, then place the beaker in a water bath at a constant temperature of 80-90℃, and use the VersaStat4 electrochemical workstation to measure the diaphragm resistance value at 80℃. The calculation of the diaphragm surface resistance is:
[0068] RS=(R1-R0)×S,
[0069] Where: RS: Surface resistance of the diaphragm (Ω·cm 2 ); R0: solution resistance between the two electrodes without a diaphragm, (Ω); R1: resistance after adding a diaphragm, (Ω); S: effective area of the diaphragm, (cm 2 ).
[0070] (2) Bending resistance test:
[0071] Take out the sample and fold it with "Z-fold". After folding, roll a weight of about 2 kg over the folded film. Then check the wrinkles and cracks on the light box. When cracks appear, record the number of times the weight rolls over.
[0072] Table 2
[0073] <![CDATA[Sheet Resistance (Ω·cm 2 )]]> Bending times Example 1 0.12 12 Example 2 0.10 10 Example 3 0.14 9 Example 4 0.13 10 Example 5 0.11 11 Example 6 0.14 13 Example 7 0.12 8 Example 8 0.16 14 Example 9 0.13 10 Example 10 0.15 9 Comparative Example 1 0.19 15 Comparative Example 2 0.11 6 Comparative Example 3 0.18 13
[0074] It can be seen from Table 2 that the diaphragms prepared in Examples 1-10 of the present application have excellent toughness and low internal resistance. Compared with Examples 1-10, the second type of binder in Comparative Example 1 does not use a halogenated polymer. Although the obtained diaphragm has many bending times and good toughness, it has a high internal resistance. The concentration of the cross-linking agent in Comparative Example 2 is too low, the cross-linking reaction is insufficient, and the toughness of the diaphragm is poor. The cross-linking time of Comparative Example 3 is too long, the density of the diaphragm is increased, the pore size is reduced, and the surface resistance of the membrane becomes larger.
[0075] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0076] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A diaphragm for alkaline water electrolysis, characterized in that: The invention comprises a base film and a coating layer provided on at least one side of the base film, wherein the preparation of the coating layer comprises the following raw material components: Inorganic particles, a first type of binder, a second type of binder, a pore former, an organic solvent and a crosslinking agent, wherein the second type of binder comprises one or more of halogenated polysulfone, halogenated polyethersulfone and halogenated polyphenylsulfone.
2. The alkaline water electrolysis diaphragm according to claim 1, characterized in that: The inorganic particles, the first type of binder, the second type of binder, the pore-forming agent and the organic solvent form a casting liquid. Based on the total mass of the raw material components of the casting liquid, the mass proportion of each component is: inorganic particles 29%-60%, first type of binder 4%-30%, second type of binder 5%-11%, pore-forming agent 0.1%-5%, organic solvent 21%-61%.
3. The alkaline water electrolysis diaphragm according to claim 1 or 2, characterized in that: The cross-linking agent includes one or more of imidazole, trimethylimidazole, bipyridine, tetramethylethylenediamine and ethylenediamine; and / or, In the repeating units of the polymer of the second type of binder, each repeating unit contains 0.5-6 halomethyl groups.
4. The alkaline water electrolysis diaphragm according to claim 1 or 2, characterized in that: The inorganic particles include one or more of ZrO2, TiO2, Mg(OH)2, Y2O3, CeO2, HfO2, Zr3(PO4)4, SiC, and BaSO4.
5. The alkaline water electrolysis diaphragm according to claim 1 or 2, characterized in that: The first type of binder includes at least one of polysulfone, polyethersulfone and polyphenylsulfone.
6. The alkaline water electrolysis diaphragm according to claim 1 or 2, characterized in that: The organic solvent includes one or more of N-methyl-2-pyrrolidone, N-ethyl-pyrrolidone, N,N-dimethylformamide, formamide, dimethyl sulfoxide, and N,N-dimethylacetamide.
7. The alkaline water electrolysis diaphragm according to claim 1 or 2, characterized in that: The pore-forming agent includes one or more of glycerol, polyvinyl pyrrolidone, polyethylene glycol, and polyvinyl alcohol.
8. The alkaline water electrolysis diaphragm according to claim 1 or 2, characterized in that: The base film includes one of polypropylene, polyethylene, polysulfone, polyphenylene sulfide, polyamide, polyethersulfone, polyphenylsulfone, polyethylene terephthalate, and polyetheretherketone.
9. A method for preparing the alkaline water electrolysis diaphragm according to any one of claims 1 to 8, characterized in that: include: The inorganic particles, the first type of binder, the second type of binder, the pore-forming agent and the organic solvent are mixed into a casting solution, and the solution is symmetrically coated on both sides of the base film to form pores and form a film to obtain an intermediate film; The crosslinking agent is dissolved in water to prepare a crosslinking agent aqueous solution with a crosslinking agent mass ratio of 5%-20%, the intermediate membrane is crosslinked in the crosslinking agent aqueous solution for 10min-30min, and then washed with water to obtain a diaphragm for alkaline water electrolysis.
10. The method according to claim 9, characterized in that The pore-forming and film-forming method adopts a non-solvent-induced phase separation method.
Citation Information
Cited By
Alkaline electrolytic water hydrogen production diaphragm based on modified cerium oxide and preparation method thereof
CN121653751A